ALGORITHMIC GOVERNANCE AND DEMOCRATIC LEGITIMACY: Rethinking Digital Co-Creation in Constitutional Law-Making - Syafri Hariansah; Laila Qhistina (Al-Risalah, 2026)
Despite the rapid digitalisation of legislative processes in Indonesia, public participation in law-making remains largely consultative and exerts limited influence on legislative outcomes. Existing scholarship predominantly frames digital participation in terms of transparency and governance innovation, overlooking its constitutional function in sustaining democratic legitimacy. This article argues that legislative processes are increasingly structured by algorithmic governance, where digital platforms not only facilitate but also filter and prioritise public input, thereby reshaping the relationship between participation and legitimacy. Using a socio-legal approach combining doctrinal analysis and comparative examination, this study analyses the regulatory framework under Law No. 12 of 2011 as amended by Law No. 13 of 2022 and evaluates Indonesia’s digital legislative platforms. The findings reveal that participation remains largely symbolic due to three structural deficiencies: the absence of binding obligations that require legislative responsiveness, a fragmented institutional design, and the opacity of algorithmic mediation. Comparative experiences from Finland, the United States, and the European Union demonstrate that participation contributes to legitimacy only when it generates enforceable institutional duties within accountable digital systems. This article advances digital co-creation as a constitutional model that redefines participation as a structural condition of legitimacy in algorithmically mediated law-making, requiring institutional arrangements that embed citizens in iterative legislative processes under conditions of algorithmic accountability.